Comparative efficacy and safety of therapeutics for elderly glioblastoma patients: A Bayesian network analysis. (August 2022) - Zhao, Binghao; Wu, Jiaming; Xia, Yu; Li, Huanzhang; Wang, Yaning; Qu, Tian; Xing, Hao; Wang, Yu; Ma, Wenbin
Abstract: Optimal management strategies for elderly glioblastoma (GBM) patients remain elusive. Overall survival (OS) and progression-free survival (PFS) in elderly newly diagnosed GBM (ndGBM) patients were analyzed with random-effects Bayesian network meta-analysis with the estimated hazard ratio (HR) with a 95% confidence interval (95% CrI). In addition, OS, PFS and adverse event (AE) data on ndGBM and recurrent GBM (rGBM) were assessed. Seventeen eligible trials with 12 on ndGBM and 5 on rGBM were identified. For the improvements it induced in the OS of elderly ndGBM patients, tumor treating field (TTF) + temozolomide (TMZ) (HR: 0.11, 95% CrI: 0.02–0.67 vs. supportive care (SPC)) ranked first, followed by TMZ + hyperfractionated radiotherapy (HFRT) (HR: 0.17, 95% CrI: 0.03–0.95 vs. SPC). For the improvements it induced in the PFS of elderly ndGBM patients, bevacizumab (BEV) + HFRT ranked first, followed by TMZ + HFRT. TMZ was observed to be more effective in O6-methylguanine-DNA-methyltransferase (MGMT) promoter-methylated ndGBM patients than HFRT and standard radiotherapy (STRT). For elderly rGBM patients, the treatments included were comparable. The rates of other neurological symptoms (16.1%) and lymphocytopenia (10.4%) were higher in ndGBM patients; lymphocytopenia (10.3%) and infection (8.1%) were higher in rGBM patients among the ≥ 3 grade AEs. TMZ-related AEs should be further considered. In conclusion, TTF + adjuvant TMZ and TMZ + HFRT are most likely to be recommended for elderly ndGBM patients. No best treatment for rGBM in elderly patients is illustrated. TMZ is identified to be more effective in elderly ndGBM patients with methylated MGMT status; however, AEs associated with TMZ-related therapy should be well considered and managed. Graphical Abstract: ga1 Highlights: TTF + adjuvant TMZ and TMZ + HFRT are likely to be recommended for elderly newly diagnosed GBM (ndGBM) patients. TMZ appears to be more effective in elderly ndGBM patients with MGMT promoter methylation. More evidence is needed for AEs with TMZ-related therapy.